Carbon fluxes and stocks in freswater wetlands in Mexico - Hernández, María Elizabeth; Moreno-Casasola Barceló, Patricia (Instituto de Ecología, A.C., 2018)
In this study, we made a review about carbon stocks and fluxes in Mexican freshwater wetlands. Data for carbon storage in roots, soil and biomass has been reported for marshes, forested wetlands and flooded grasslands in southeast Mexico: Veracruz, Chiapas and Yucatán. The largest carbon stock in freshwater wetlands is the soil (150 Mg C ha-1 a 650 Mg C ha-1) and the forested wetlands showed the highest values. The carbon stock in the biomass ranges from 10 Mg C ha-1 to 162 Mg C ha-1, and forested wetlands showed the highest values. Carbon fluxes measured as litter fall has been reported for forested wetlands in Veracruz (6 Mg C ha-1 year-1 a 9 Mg C ha-1 year-1) only. Methane and carbon dioxide fluxes ranged from 0.01 mg C m-2 d-1 to 1244 mg C m-2 d-1, and 0.009 g C m-2 d-1 to 11 g C m-2 d-1 respectively for Veracruz and Tabasco wetlands. Such carbon fluxes increased up to ten times, when wetlands are transformed to grasslands. It is concluded that the number of publications and study sites on carbon dynamics in Mexican freshwater wetlands is still very small. Therefore, it is necessary to increase the research in this area and enact laws that protect these important carbon sinks.